Reaction dynamics and nuclear structure of light exotic nuclei - Di Pietro Alessia (EPJ Web of Conferences)
The paper explores reaction experiments using low-energy post-accelerated radioactive beams to examine the influence of halo structures and neutron excess on reaction dynamics. Results of reactions induced by neutron-halo and proton-halo nuclei are compared, highlighting differences in the reaction dynamics that stem from variations in nuclear structure. Additionally, the study addresses neutron-rich nuclei, focusing on the presence of resonances in the elastic scattering excitation function, which are attributed to the extended surface layer characteristic of these nuclei.